Reluctant recyclers: Social interaction in responsibility ascription - Kjell Arne Brekke; Gorm Kipperberg; Karine Nyborg (University of Oslo, Department of Economics, 2007)
Several studies have demonstrated that individual contributions to public goods are increasing in others' contributions. The underlying causes for this, however, are not yet fully understood. We present a model of duty-orientation in which moral responsibility is learned through observations of others' behavior. Since, in our model, responsibility is a burden, we hypothesize that individuals will be reluctant to accept responsibility based on uncertain information. Econometric analysis of data from a survey on households' glass recycling indicates that perceived responsibility is a major determinant for reported recycling; that responsibility ascription is influenced by beliefs about others' behavior; and that people are indeed reluctant to accept responsibility based on uncertain information.
Keywords: D11; D12; D64; Q53; 330; Voluntary contributions; duty-orientation; recycling; joint FIML estimation; Soziale Beziehungen; Altruismus; Verantwortung; Selbstverpflichtung; Unvollkommene Information; Schätzung; Recycling; Norwegen